Diagnostic methods and emerging treatments for adult neuronal ceroid lipofuscinoses (Kufs disease). (3rd June 2017) - Magrinelli, Francesca; Pezzini, Francesco; Moro, Francesca; Santorelli, Filippo M.; Simonati, Alessandro
ABSTRACT: Introduction : Adult-onset neuronal ceroid lipofuscinoses (ANCL) are a group of rare inherited neurodegenerative diseases of early adulthood, named after the presence of intralysosomal autofluorescent lipopigment with characteristic ultrastructural features in neurons and other cell types. Over the last decade, six ANCL genes have been identified, three of them being related to exclusively adult-onset phenotypes, the remaining three shared with childhood-onset NCL (CNCL). Areas covered : Even in the molecular era, the contribution of neuropathological assessment is essential since genetic heterogeneity foresees new genes to be detected and validated. No disease-modifying therapy (DMT) is available for neuronal ceroid lipofuscinoses (NCL), but patients may benefit from improved symptomatic and supportive treatments, and recent advances in cellular and molecular biology (utilizing both cellular and animal models of the disease) have provided important contributions to the knowledge of NCL pathophysiology. DMT strategies aim to prevent storage formation and/or deplete accumulated substrate; few of them have already been translated into clinical practice in CNCL only. Expert opinion : The complexity of pathophysiological mechanisms underlying NCL, such as neuronal excitotoxicity, unfavourable condition of the neuropil and enhanced vulnerability of the affected cells, requires the identification of multiple targets suitable for treatments to prevent neuronal progressive dysfunction and death.